FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN - Rifka Nabila; Dimas Wicaksono (AKRUAL : Jurnal Akuntansi dan Keuangan, 2023)
This study aims to analyze the effect of accounting information systems, internal controls, and the use of information technology on the quality of financial reports. The population in this research is the BSI Employee Cooperative, BNI Syariah and employee Cooperatives in the DKI Jakarta area. This research uses primary data which is measured using a Likert scale. The method for distributing questionnaires uses Google Form. Sampling was carried out using purposive sampling and the total sample was 37 respondents. Analyzed using SmartPLS version 4.9.5. The results showed that the accounting information system and internal control had a significant positive effect on the quality of financial reports, while the use of information technology did not have a significant effect on the quality of financial reports.